Factors Affecting Burnout Syndrome Among Nurses: A Systematic Review - Rizal Tri Ardiansyah; Fetreo Negeo Putra; Hari Soebagyo; Basilius Yosepfus Weu (Universitas Airlangga, 2019)
Background: Burnout syndrome is due to the fatigue felt from work, both physically and mentally. Work fatigue experienced by the health care team, especially the nurses, can threaten patient safety. There needs to be actions or policies put in place to decrease the level of nurse burnout syndrome. Before setting the policies or actions, it is important to know the factors that affect the occurrence of burnout syndrome. The purpose of this paper is to analyze the factors that influence the occurrence and incidence of burnout syndrome.Method: The authors specified the topics and keywords used to search the literature, which in turn allowed for the seeking and obtaining of the appropriate literature criteria. The search found 15 pieces of literature.Result: There are several factors that cause burnout syndrome, but the most common factor in the working environment was the poor working conditions and motivation factors of nursing itself.Conclusion: Based on the results above, we can reduce burnout syndrome with modifications in the working environment or improving the nurse’s motivation through policies, dependent on the institution.